Naphthalene diimide-difluorobenzene-based polymer acceptors for all-polymer solar cells. Issue 22 (6th March 2017) - Deng, Ping; Ho, Carr Hoi Yi; Lu, Yong; Li, Ho-Wa; Tsang, Sai-Wing; So, Shu Kong; Ong, Beng S.
Abstract : Two new difluorobenzene-naphthalene diimide polymer acceptors, P1 andP2, were developed as polymer acceptors for all-polymer solar cells. Abstract : Regio-random (P1 ) and -regular (P2 ) difluorobenzene-naphthalene-containing polymer acceptors were developed for bulk-heterojunction all-polymer solar cells (all-PSCs).P2 exhibited significantly higher crystallinity in thin films, providing high spectral absorptivity and electron mobility thanP1 . When used in all-PSC devices, P2 afforded a respectably higher power conversion efficiency of over 5%.